Psychological and pedagogical conditions of integration of immigrants into the German society - Krutova-Soliman, Natalja; Romanenko, Nadezhda M.; Shishlova, Ekaterina E. (Linguistics and Culture Review, 2021)
Among the new migration challenges of the modern world, perhaps the most acute is the issue of the integration of migrants. As a result of globalisation, events in the world are connected as communicating vessels and, the more unresolved problems in Africa or the Middle East, the stronger the desire of those in need of assistance to move to industrial countries with humane social welfare policies. In this regard, public interest in the problems of the European Union, including Germany, related to the influx of refugees through the Balkan route at the turn of 2015, is holding. The purpose of this paper is to present the results of a study conducted with students of integration courses at the People’s University of Frankfurt am Main (VHS Frankfurt am Main) in the period from 2017 to 2020, and to demonstrate specially created psychological and pedagogical conditions that contribute to the development of a higher and better level of ability to integrate immigrants into the cultural and linguistic environment of Germany during the acquisition of the German language.